2021
DOI: 10.1007/s40618-021-01533-4
|View full text |Cite
|
Sign up to set email alerts
|

The genetic background and vitamin D supplementation can affect irisin levels in Prader–Willi syndrome

Abstract: Background Prader–Willi syndrome (PWS) is associated to distinctive clinical symptoms, including obesity, cognitive and behavioral disorders, and bone impairment. Irisin is a myokine that acts on several target organs including brain adipose tissue and bone. The present study was finalized to explore circulating levels of irisin in children and adult PWS patients. Methods Seventy-eight subjects with PWS, 26 children (15 females, mean age 9.48 ± 3.6 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 46 publications
(50 reference statements)
1
15
2
Order By: Relevance
“…Hirsch et al [ 32 ] found salivary irisin was markedly elevated in adults with PWS compared with healthy controls matched by BMI, but no differences in irisin levels after resistance exercise in a study of 11 young patients with PWS [ 58 ]. Our findings are at odds with those reported by Faienza et al [ 31 ], who found no difference in irisin levels between controls and a sample of 73 subjects with PWS, 52 of whom were adults, and with those reported by Mai et al [ 30 ], who found similar levels in obese individuals with PWS and lean healthy controls, but higher levels in obese individuals without PWS [ 30 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Hirsch et al [ 32 ] found salivary irisin was markedly elevated in adults with PWS compared with healthy controls matched by BMI, but no differences in irisin levels after resistance exercise in a study of 11 young patients with PWS [ 58 ]. Our findings are at odds with those reported by Faienza et al [ 31 ], who found no difference in irisin levels between controls and a sample of 73 subjects with PWS, 52 of whom were adults, and with those reported by Mai et al [ 30 ], who found similar levels in obese individuals with PWS and lean healthy controls, but higher levels in obese individuals without PWS [ 30 ].…”
Section: Discussioncontrasting
confidence: 99%
“…By contrast, irisin not only positively regulates muscle growth, but also can convert white adipose tissue to brown fat [ 28 ], increasing energy expenditure and improving glucose tolerance. Discordant myokine levels have been reported in studies in patients with PWS [ 29 , 30 , 31 , 32 ].…”
Section: Introductionsupporting
confidence: 56%
“…Mai et al also reported that PWS patients and controls had similar circulating irisin levels [ 46 ]. More recently, hypovitaminosis D was found by our group in a cohort of PWS patients [ 47 ]. Interestingly, irisin levels of those not supplemented with 25(OH)-Vitamin D were lower than levels detected in both controls and supplemented patients.…”
Section: Irisin In Prader-willi Syndrome (Pws)mentioning
confidence: 99%
“…Interestingly, irisin levels of those not supplemented with 25(OH)-Vitamin D were lower than levels detected in both controls and supplemented patients. Of note, a multiple regression analysis showed that irisin levels in both pediatric and adult PWS were predicted by genetic background and levels of 25(OH)-Vitamin D [ 47 ]. However, further studies are needed to understand the relationship between irisin and 25(OH)-Vitamin D and whether this interaction is influenced by disease type.…”
Section: Irisin In Prader-willi Syndrome (Pws)mentioning
confidence: 99%
“…PWS individuals are protected to some degree from the adverse metabolic effects of VAT. Fatty liver is rare in PWS and PWS individuals have less insulin resistance compared to individuals with non-syndromic obesity [ 2 5 ]. Nutritional intervention even without growth hormone treatment has been shown to maintain VAT within the normal reference range [ 6 ].…”
mentioning
confidence: 99%